1976
DOI: 10.1042/bj1600085
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic synthesis of carnitine from protein-bound trimethyl-lysine. Lysosomal digestion of methyl-lysine-labelled asialo-fetuin

Abstract: The biosynthesis of carnitine in the rat was studied by following the metabolism of two radioactive derivatives of asialo-fetuin. The first contained 14C-labelled methyl groups covalently bound to the 6-N-amino fraction of its lysine residues as 6-N-monomethyl- and dimethyl-lysine. By treating this protein with iodomethane, a second derivative was produced in which the radioactivity was preferentially incorporated as 6-N-[Me-14C]-trimethyl-lysine. These desialylated glycoproteins, like other asialo-proteins, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1980
1980
2009
2009

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(23 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…Carnitine ultimately derives from the es sential amino acids lysine and methionine. The pathway of carnitine biosynthesis in mammals seems to be unique in that an obli gate intermediate, trimethyllysine is derived only from post-translational modification of peptide chains and subsequent breakdown of these proteins [48,49], However, in healthy volunteers oral administration of 5 g of ly sine was found to produce progressive rise in plasma trimethyllysine with an increase of plasma and urinary carnitine levels suggest ing the possibility of a non-peptidyl pathway of biosynthesis [50,51).…”
Section: Dietary Intakementioning
confidence: 99%
“…Carnitine ultimately derives from the es sential amino acids lysine and methionine. The pathway of carnitine biosynthesis in mammals seems to be unique in that an obli gate intermediate, trimethyllysine is derived only from post-translational modification of peptide chains and subsequent breakdown of these proteins [48,49], However, in healthy volunteers oral administration of 5 g of ly sine was found to produce progressive rise in plasma trimethyllysine with an increase of plasma and urinary carnitine levels suggest ing the possibility of a non-peptidyl pathway of biosynthesis [50,51).…”
Section: Dietary Intakementioning
confidence: 99%
“…Similarly, it has been shown that dietary carnitine enhances growth of rats fed a lowmethionine diet, indicating that dietary carnitine may possibly have a methionine-sparing effect (Khairallah and Wolf, 1965). On the other hand, protein that contains methylated lysine is required for carnitine synthesis (Labadie et al, 1976). Bremer (1961) showed that less of the methionine methyl groups is incorporated into carnitine.…”
Section: Regulation Of Carnitine Homeostasismentioning
confidence: 99%
“…The dry residue from urines were obtained through a cleanup procedure based on that of Labardie et al (15).…”
Section: Sample Treatmentmentioning
confidence: 99%